Academic production in the field of combat sports: the case of judo and the studies of the principles and values of the sport - de Jesus, Glauber Bedini; Impolcetto, Fernanda Moreto [UNESP] (FapUNIFESP (SciELO), 2022)
Aim: The purpose of the study was to carry out a survey and analysis of the scientific production of judo, specifically the contents that discuss the principles and values of this sport, to understand the contexts of its production at the national and international levels. Methods: A state of the art literature review was used to analyze seven national journals of Physical Education and five specialized in the area of combat sports, from their first editions up until the year 2021. Results: The results indicated that judo production has grown mainly in the last decade. In both national and specialized journals, the analyzed productions (n = 69 and n = 410, respectively) were concentrated in biodynamics (57.97% and 72.93%), followed by the sociocultural (30.43% and 23.41%) and pedagogical areas (11.60% and 3.66%). Articles on principles and values accounted for only 8.35% of judo production, of which 47.50% were written entirely in English, 42.50% in Japanese with only abstracts in English, and a measly 10% in Portuguese, confirming the diffi-culty in finding information on the topic. This aridity may be the result of the technical-sports perspective that drives scientific research in the area of biodynamics and the language barriers of publications concentrated in English and Japanese. Conclusion: It is suggested that actions by the regulatory institutions be taken to encourage both research and greater access to the conceptual and attitudinal knowledge of judo, extrapolating the offer of bodily knowledge and approaching the democratic and integral educational process that is expected.
Keywords: combat sports; content; democratization; judo; teaching